Ionic Liquid-Based Microwave-Assisted Extraction: Fast and Green Extraction Method of Secondary Metabolites on Medicinal Plant - Ahmad, Islamudin; Yanuar, Arry; Mulia, Kamarza; Mun’im, Abdul (Pharmacognosy Reviews)
Background: Ionic liquid‑based microwave‑assisted extraction (IL‑MAE) is one of the non-conventional extraction methods that has been developed and applied in recent years. Some studies have reported the success of this approach for extracting the target compound (secondary metabolites) from medicinal plants optimally. Objectives: This review paper aimed to provide detail information about the application of the IL‑MAE method as a fast and green extraction of a secondary metabolite from the medicinal plant. Materials and Methods: The literature published on IL‑MAE was searched and collected using online resources from the electronic databases including Google Scholar, DOAJ, PubMed, ScienceDirect, and Scopus. Results: This review highlights the role of IL as a green solvent, the basic principles, mechanisms of MAE, and its utilization of natural product extraction. Furthermore, this review explained about the application of the IL‑MAE method to extract secondary metabolite (particularly the targeted compound) from a medicinal plant, and a brief extraction mechanism of IL‑MAE using Fourier‑transform infrared spectroscopy and scanning electron microscopy. Conclusion: The application of IL‑MAE method has successfully performed to extract the targeted secondary metabolite from a natural product, where the extraction process to be rapid, efficient, and green.
Keywords: Ionic liquid‑based microwave‑assisted extraction; ionic liquids; medicinal plant; microwave‑assisted extraction; secondary metabolite